The whispering skull - Stroud, Jonathan (Stroud, Jonathan. Lockwood & Co., 2014)
"Lockwood & Co. are hired to investigate Edmund Bickerstaff, a Victorian doctor who reportedly tried to communicate with the dead, while Lucy is distracted by urgent whispers coming from the skull in a ghost jar"--